2014
DOI: 10.4174/astr.2014.87.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic factors affecting tumor recurrence after hepatic resection in colorectal liver metastases

Abstract: PurposeHepatic resection is a standard method of treatment for colorectal liver metastases (CRLM). However, the pathologic factors of metastatic lesions that affect tumor recurrence are less well defined in CRLM. The aim of this study was to evaluate the risk factors for recurrence of CRLM, focusing on histopathologic factors of metastatic lesions of the liver.MethodsFrom January 2003 to December 2008, 117 patients underwent curative hepatic resection for CRLM were reviewed. Tumor size and number, differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 15 publications
1
28
0
2
Order By: Relevance
“…Vascular invasion can occur through portal or hepatic veins . Some studies differentiated between portal vein and hepatic vein invasion, whereas others did not establish a prognostic distinction . Shirabe et al .…”
Section: Vascular Invasionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vascular invasion can occur through portal or hepatic veins . Some studies differentiated between portal vein and hepatic vein invasion, whereas others did not establish a prognostic distinction . Shirabe et al .…”
Section: Vascular Invasionmentioning
confidence: 99%
“…17 Some studies differentiated between portal vein and hepatic vein invasion, 17,18,65 whereas others did not establish a prognostic distinction. 63,64,66 Shirabe et al 65 and Sasaki et al 17 studied portal vein invasion and hepatic vein invasion separately among patients with CRLMs who underwent liver resection, and noted that neither was a significant prognostic factor. In contrast, Yamamoto et al 18 analysed portal and hepatic vein invasion, and noted that both were independent factors associated with poor prognosis after liver resection.…”
Section: Vascular Invasionmentioning
confidence: 99%
“…More than half of CRC patients will develop metastases during the course of the disease, and the quarter has distant metastases at diagnosis, mainly in the liver . Although liver surgery can cure metastatic colorectal cancer (mCRC) in some cases, tumor recurrence affects 50% to 75% of the patients within 2 years . The hypothetical mechanisms of recurrence include remaining cancer cells or occult micrometastases unseen at the time of surgery .…”
Section: Introductionmentioning
confidence: 99%
“…As the liver is the most common metastatic site for CRC, many different histomorphological features have been examined and proposed to stratify patients with colorectal liver metastases (CLM) into distinct prognostic groups . The prognostic impact of a variety of factors including the presence of intrahepatic lymphatic vascular invasion, vascular invasion, infiltrative tumor border, the absence of tumor pseudocapsule, and peritumoral and intratumoral inflammatory infiltrate has been investigated . In contrast, while examined in primary CRC tumors, only one study on TB has been reported among patients with CLM, and the prognostic implications of PDC among patients with CLM has not been examined to date.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 The prognostic impact of a variety of factors including the presence of intrahepatic lymphatic vascular invasion, vascular invasion, infiltrative tumor border, the absence of tumor pseudocapsule, and peritumoral and intratumoral inflammatory infiltrate has been investigated. 17,[19][20][21][22][23] In contrast, while examined in primary CRC tumors, only one study on TB has been reported among patients with CLM, 23 and the prognostic implications of PDC among patients with CLM has not been examined to date. Therefore, the objectives of the current study were to assess the presence and incidence of TB and PDC among CLM, as well as define the prognostic impact of TB and PDC.…”
mentioning
confidence: 99%